Finite Element Analysis of the Temperature Field of Face Gear Dish Wheel Grinding - Ming Xingzu; Zhao Lei; Wang Wei; Li Mande (Jixie chuandong)
According to the principle of face gear dish wheel grinding,by using the theory of instantaneous contact ellipse,the grinding basic parameters are solved,the finite element model of gear grinding temperature field is set up and the gear grinding transient temperature field finite element simulation is carried out.Through the simulation and experimental analysis,the basis for basic parameter optimization,improve the quality of grinding and further research of face gear grinding temperature field is provided.